Compositional Dependence of DNA Partitioning in a Poly(Ethylene Glycol)–Ficoll Aqueous Two-Phase System - Tasdiq Ahmed; Adya Verma; Alexandra T. Patterson; Mark P. Styczynski; Shuichi Takayama (Chemistry)
Aqueous two-phase systems (ATPSs) have long been used for the facile and rapid extraction of biomolecules of interest. Selective partitioning of DNA is useful for nucleic acid purification and in the design of novel sensing technologies. This paper investigates the partitioning of a plasmid within a poorly understood ATPS comprising the polymers poly(ethylene glycol) (PEG) 35 kDa and Ficoll 400 kDa. The focus is placed on dissecting the compositional effects of the ATPS—that is, whether set concentrations of physiological ions or the polymers themselves can tune DNA phase preference and strength of partitioning. The work here uncovers the antagonistic effects of magnesium and ammonium ions, as well as the role that phase-forming polymer partitioning plays in plasmid enrichment. Testing the ions in conjunction with different ATPS formulations highlights the complexity of the system at hand, prompting the exploration of DNA’s conformational changes in response to polymer and salt presence. The work presented here offers multiple optimization parameters for downstream applications of PEG–Ficoll ATPSs, such as in vitro transcription/translation-based biosensing, in which performance is heavily dependent upon nucleic acid partitioning.